Implementation of Contextual Teaching and Learning Strategy in Improving Learning Outcomes of the Subject of Aqidah Akhlak at MI Darul Istiqomah Srigading - Wardani, Yuyun; Yulistyaningsih; Yumna; Yuniatun; Yuliati (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to improve student learning outcomes in the subject of Akidah Akhlak through the application of the Contextual Teaching and Learning strategy. The method used is Classroom Action Research which is carried out in two cycles. The subjects of the study were grade 5 students of MI Darul Istiqomah Srigading. Data collection techniques include observation, interviews, and learning outcome tests. The results of the study showed that the application of the CTL strategy was able to increase students' active involvement in the learning process. In addition, there was a significant increase in student learning outcomes after the implementation of this strategy, as indicated by the increase in the average class value from the first cycle to the second cycle. This success is due to a more contextual learning approach, linking material to students' real experiences so that it is easier to understand. Thus, the CTL strategy has proven effective in improving students' understanding and learning outcomes in the subject of Akidah Akhlak. It is hoped that this study can be a reference for teachers in developing more innovative and interactive learning methods.